Long-Read Sequencing Reveals Genetic Adaptation of Bartonella Adhesin A Among Different Bartonella henselae Isolates - Thibau, Arno; Hipp, Katharina; Vaca, Diana J.; Chowdhury, Sounak; Malmström, Johan; Saragliadis, Athanasios; Ballhorn, Wibke; Linke, Dirk; Kempf, Volkhard A. J. (Frontiers in Microbiology, 2022)
Bartonella henselae is the causative agent of cat scratch disease and other clinical entities such as endocarditis and bacillary angiomatosis. The life cycle of this pathogen, with alternating host conditions, drives evolutionary and host-specific adaptations. Human, feline, and laboratory adapted B. henselae isolates often display genomic and phenotypic differences that are related to the expression of outer membrane proteins, for example the Bartonella adhesin A (BadA). This modularly-structured trimeric autotransporter adhesin is a major virulence factor of B. henselae and is crucial for the initial binding to the host via the extracellular matrix proteins fibronectin and collagen. By using next-generation long-read sequencing we demonstrate a conserved genome among eight B. henselae isolates and identify a variable genomic badA island with a diversified and highly repetitive badA gene flanked by badA pseudogenes. Two of the eight tested B. henselae strains lack BadA expression because of frameshift mutations. We suggest that active recombination mechanisms, possibly via phase variation (i.e., slipped-strand mispairing and site-specific recombination) within the repetitive badA island facilitate reshuffling of homologous domain arrays. The resulting variations among the different BadA proteins might contribute to host immune evasion and enhance long-term and efficient colonisation in the differing host environments. Considering the role of BadA as a key virulence factor, it remains important to check consistently and regularly for BadA surface expression during experimental infection procedures.